2022-RA-793-ESGO TROP-2 expression and the tumor immune-microenvironment in cervical cancer. (20th October 2022) - Chiba, Yohei; Yazaki, Shu; Kojima, Yuki; Yoshida, Hiroshi; Takamizawa, Shigemasa; Kitadai, Rui; Saito, Ayumi; Okuma, Hitomi Sumiyoshi; Nishikawa, Tadaaki; Shimoi, Tatsunori; Sudo, Kazuki; Noguchi, Emi; et al.
Abstract : Introduction/Background: Trophoblast Cell Surface Antigen 2 (TROP-2) is a transmembrane glycoprotein that is overexpressed in various cancers. Moreover, TROP-2 has immunologic relevance, as a target for tumor reactive T-cells. We performed a pilot study of 123 cervical cancers to test whether TROP-2 expression may be associated with tumor immune-microenvironment. Methodology: We performed immunohistochemical analysis of whole tumor sections from patients with cervical cancer who underwent primary surgery between 2000 and 2020 at our institution. TROP-2 expression was evaluated using anti-TROP-2 monoclonal antibody clone MAB650. Immune biomarkers including PD-L1 (22C3), CD3 (PS1), and CD8 (4B11) were also evaluated. TROP-2 and PD-L1 positive was defined as H-score ≥10 and combined positive score (CPS) ≥1, respectively. Each whole tumor section was evaluated for intratumoral tumor-infiltrating lymphocytes (TILs) by using a 40× objective lens, and 5 independent areas with the most abundant TILs were selected. The association between TROP-2 expression and immune biomarkers was analyzed. Results: The cohort consisted of squamous cell carcinoma (SCC) (54.5%) and non-SCC (45.5%). In IHC samples, TROP-2 positive was identified in 84.6% and more commonly expressed in SCC (SCC vs. non-SCC; 97.0% vs. 69.6%, p<0.001). Spearman's correlation analysis showed significant and positive correlations between TROP-2 H-score and immune markers (CD3+TILs, r=0.295, p<0.001; CD8+TILs, r=0.267, p=0.001; PD-L1 CPS, r=0.178, p=0.025). None of the other clinicopathological features were associated with T cell infiltration in the study sample. The percentage of TROP2-positive patients in the PD-L1-positive or CD3-High group was 89.2% and 93.9%, respectively. After a median follow-up of 67.8 months, TROP-2 expression showed no correlation with DFS and OS (log rank test, p =0.478 and 0.071). Conclusion: Expression of TROP-2 in cervical cancer is associated with increased levels of intratumoral TILs, indicating the potential therapeutic target for TROP-2 targeted antibody-drug conjugate alone or in combination with immune checkpoint inhibitors.